Reforming Egypt’s Alternative Child Care System Through Deinstitutionalization: An Assessment of the Current Status and Readiness to Change in the Residential Care Sector - Elbawab, Dina (AUC Knowledge Fountain, 2024)
The main objective of this study was to assess the current status and readiness of the sector of residential care institutions for children to take part in the deinstitutionalization of children in alternative care in Egypt. The assessment was carried out using an adapted version of the Community Readiness Model (CRM), a tool developed by the Tri-Ethnic Center at Colorado State University. Accordingly, the assessment comprised semi-structured interviews with fourteen key informants to assess the following six readiness dimensions: efforts, knowledge of the efforts, leadership, community climate, knowledge of the issue, and resources related to the issue. The study briefly examined in tandem the potential role of residential care institutions in deinstitutionalization. The data analysis was done using the scoring process prescribed in the model to measure readiness. In addition, a qualitative framework analysis was conducted to support the CRM scores. The findings mainly demonstrated that at the policy level, the government and some civil society partners, including a few from the residential child care sector, have been invested in deinstitutionalization and have continued to take action toward it since 2014; however, more efforts targeted at existing institutions are required to ensure a smooth transition. It was revealed that resistance is prevalent among these institutions as most are not adequately engaged, feel threatened, and lack understanding about deinstitutionalization’s true significance and scope. Based on the findings, practical insights for engaging and transforming residential child care and avenues for future research were discussed.